Risk Factors for Mortality of Patients with Covid-19 in RSJPD Harapan Kita, Jakarta - Zhara Juliane; Asri Chasanah Adisasmita; Yoga Yunadi (Jurnal Respirologi Indonesia, 2022)
Abstract Background:TheCovid-19 disease has caused significant morbidity and mortality worldwide since Covid-19 was first reported in December 2019. More intense kinds of the disorder main to loss of life arise greater regularly in older sufferers and people with more than one comorbidities. This study  aims  to determine the risk factors associated with death in Covid-19 patients at RSJPD Harapan Kita.Methods:A total of 500 patients with a positive result on the Covid-19 polymerase-chain-reaction (PCR) test from RSJPD Harapan Kita were analyzed. The Demographic, clinical, and outcome data were extracted from the hospital's medical record system.  To explore the risk factors associated with mortality, univariable and multivariable logistic regression analyses were used.Results:Of the 500 patients included in this study, 110 (22%) died in the hospital. The multivariate regression analysis showed that age³65 years (adjusted odds ratio (aOR), 2,624; (95% CI: 1,552 – 4,435), chronic lung disease (aOR, 8,173; 95% CI: 3,834 – 17,422), chronic kidney disease (aOR,2,523; 95% CI: 1,358 – 4,689), and cardiovascular disease (aOR, 3,149; 95% CI: 1,763 – 5,624) had been recognized as risk factors of mortality among Covid-19 patients. Conclusion: Age ³65 years, chronic lung disease, chronic kidney disease patients, and cardiovascular disease had been recognized as risk factors of mortality among Covid-19 patients in RSJPD Harapan Kita. More research on the risk factors related to Covid-19-associate death is had to manage ailment development and to enhance its treatment.Keywords: Covid-19, Risk Factors, Mortality, Comorbidities.